A market leader strategy in a medical tourism industry: a case study of Puteri Specialist Hospital, Johor Bahru / Mohd Faizal Aziz, Noor Azreena Ibrahim, Nor Haryani Mohd Tahir - Aziz, Mohd Faizal; Ibrahim, Noor Azreena; Mohd Tahir, Nor Haryani (2013)
The term medical tourism has come to embrace all facets of consumers seeking treatment, improvement or change through medical or wellness practices -provided they cross an international border to do so. This study aims to highlight what strategies that should be pursued by PSH in order to become market leader in medical tourism industry. There are 4 main factors which determine the success of medical tourism; cheaper cost, technology advancement, hospital accreditation and staff competency. A set of questionnaires were distributed among medical tourist seeking treatment at PSH to gauge feedback from the patient pertaining to their experience and satisfaction level. An interview with marketing executives of PSH was also conducted to help researcher to understand the medical tourism activities more deeply. In a service industry, the most important aspect is the service experience to the customers. To remain competitive and continue to be the preferred choice, organizations must aim to create a compelling service experience, in order to ensure customer's satisfaction and continued loyalty.